Firm-Level Decomposition of Energy Consumption in Turkish Manufacturing Industry - Sahin, Sebnem (World Bank, Washington, DC, 2017)
Energy efficiency in industry is a crucial topic for Turkey, as the country has an import dependency of 80 percent in energy. Although the importance of enhancing energy efficiency in industry is widely acknowledged, there has not been any study examining the energy efficiency in Turkish industry at micro level. Employing a sound decomposition methodology on a firm-level data set of manufacturing firms, this paper documents that there was a significant decrease in the energy intensity of firms over 2005-12. In contrast, structural change across manufacturing sectors and across firms within sectors had positive but limited effects on the overall energy efficiency over the period.